A Discussion of Christopher H. Achen and Larry M. Bartels' Democracy for Realists: Why Elections Do Not Produce Responsive Government. Issue 1 (15th March 2017) - Roberts, Neil
Abstract : Liberal democracy is often viewed by its supporters as a system of government that responds to the informed and rational preferences of the public organized as voters. And liberal democracy is often viewed by its critics as a system that fails to respond to the informed and rational preferences of its citizens. In this book Larry Bartels and Chris Achen draw on decades of research to argue that a "realistic" conception of democracy cannot be centered on the idea of a "rational voter, " and that the ills of contemporary democracies, and especially democracy in the U.S., must be sought in the dynamics that link voters, political parties and public policy in ways that reproduce inequality. "We believe, " write the authors, "that abandoning the folk theory of democracy is a prerequisite to both greater intellectual clarity and real political change. Too many democratic reformers have squandered their energy on misguided or quixotic ideas."